PENGARUH IKLIM MIKRO DI BEBERAPA KETINGGIAN TEMPAT TERHADAP AKTIVITAS FISIOLOGIS, PERTUMBUHAN, HASIL DAN RENDEMEN MINYAK KELAPA SAWIT - , EKA LISTIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to determain the effect of microclimate on physiological studies, growth, productivity and quality of oil palm include oil extraction rate, carotene content and Free Fatty Acid (FFA) content in some of altitude. The experiment was conducted at four location in 50, 368, 693 and 865 m above sea level which located in North Sumatera area. The research was arranged using Randomized Block Design of Tenera at 7 â 8 years plant. The results showed that the highest photosynthesis rate at 368 m asl, while the lowest photosynthesis rate at 865 m asl is 53,8 Î¼mol CO2 mËÂ²sËÂ¹. The growth of oil palm in high altitude which include the rachis length, leaf area index, leaf dry weight, plant height, trunk volume and trunk dry weight have higher values than oil palm in low altitude. Oil palm plantation in high altitude produce heavier bunches compared with low altitude, but has a smaller number of bunches so resulting low potential productivity. The highest productivity reached 28,5 tonnes FFB/ha/year in high altitude oil palm cultivation at 368 m asl. The highest oil extraction rate of 25,9% is reached in 50 m asl. The highest carotene content 590,8 ppm and the highest harvest indext 0,39 reached by oil palm plantation at low altitude in 368 m asl.